2022
DOI: 10.3389/fnins.2022.930765
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Brain Changes in Patients With Classic Trigeminal Neuralgia: A Combination of Voxel-Based Morphometry and Resting-State Functional MRI Study

Abstract: ObjectivesBrain structural and functional abnormalities have been separately reported in patients with classic trigeminal neuralgia (CTN). However, whether and how the functional deficits are related to the structural alterations remains unclear. This study aims to investigate the anatomical and functional deficits in patients with CTN and explore their association.MethodsA total of 34 patients with CTN and 29 healthy controls (HCs) with age- and gender-matched were recruited. All subjects underwent structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Thalamus atrophy has been shown in various chronic pain conditions in prior investigations. Previous research studies have also shown that the thalamus anatomy was associated with neuropathic pain, and the level of atrophy was correlated with pain intensity in chronic pain patients (47)(48)(49)). An explanation for the atrophy of the gray matter in the thalamus could be the overactivation caused by excitotoxins and inflammatory agents (50-52).…”
Section: Brain Regionsmentioning
confidence: 87%
“…Thalamus atrophy has been shown in various chronic pain conditions in prior investigations. Previous research studies have also shown that the thalamus anatomy was associated with neuropathic pain, and the level of atrophy was correlated with pain intensity in chronic pain patients (47)(48)(49)). An explanation for the atrophy of the gray matter in the thalamus could be the overactivation caused by excitotoxins and inflammatory agents (50-52).…”
Section: Brain Regionsmentioning
confidence: 87%
“…Due to individual differences in pain intensity and negative emotion in patients with TN, the study of brain structure allows for a more direct correlation of changes with pain and negative emotion. There is ample evidence supporting the presence of white matter structural abnormalities in patients with TN ( Zhang et al, 2020 ; Liu et al, 2022 ). In our study, we identified white matter regions in the TN group with abnormally lower FA values including the genu of corpus callosum (CC), splenium of CC, tapetum of the CC, bilateral middle cerebellar peduncle (MCP), bilateral cerebral peduncle, left posterior thalamic radiation, bilateral anterior limb of internal capsule, and left posterior limb of internal capsule, compared with the HC group.…”
Section: Discussionmentioning
confidence: 99%
“…CTN is known as the most severe pain that humans can endure. Currently, most studies on the brain function of CTN patients are based on the cross-sectional rs-fMRI ( Xiang et al, 2019 ; Wu M. et al, 2020 ; Zhu et al, 2020 ; Li et al, 2021 ; Zhang et al, 2021 ; Liu et al, 2022 ). Several studies are based on the task state of TN with fewer subjects, including one case report which studied the local brain function ( Borsook et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%